EVALUASI PEMBERDAYAAN MASYARAKAT PETANI MELALUI PROGRAM SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SLPTT) PADI NON HIBRIDA (Studi Kasus Desa Kamal Kecamatan Arjasa Kabupaten Jember) - NAJMAH FAIZAH (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Community development program needs high synergy of various parties, included program of SLPTT of non hybrid rice. This research has aimed to evaluate such program such as level of farmer participation in group meeting, evaluate non hybrid rice productivity in farmer group and evaluate the strong and weakness factor of its program. The result shows participation level of farmer group member on this program is various, where farmer group of farming is highest.